KEBERHASILAN USAHA DITINJAU DARI BALANCE SCORECARD - OKTAVINI, RAHAYU WANDA; ANIMAH, ANIMAH; MARIADI, YUSLI (Universitas Mahasaraswati K. Mataram, 2024)
This research aims to develop a system for measuring the organizational performance of real estate development companies based on the concept of Balance Scorecard (BSC) and Analytical Hierarchy Process (AHP) at PT. Meka Asia Property. This research is a type of quantitative research with a descriptive approach. This research uses primary data and secondary data with several data collection methods including interviews, questionnaires, literature studies and documentation. The research results show that PT. Meka Asia Properti has performed well. Judging from the average score obtained, it is 3.7 which is included in